Integration of Knowledge Based on Local Wisdom Into the National Curriculum Through Blended Learning in Vocational School - R. Madhakomala; Sisca Cletus Lamatokan; Eric Hermawan (ASIAN PUBLISHER, 2024)
Regional local wisdom has values and knowledge that can be integrated into the school curriculum. Vocational education, especially Vocational High Schools (SMK), has the responsibility to produce professional workforce according to the demands of stakeholders. The industrial world requires human resources who have life skills as added value. The role of local-based knowledge that is integrated into the school curriculum aims to not only increase the value and economy of the region, but also prepare graduates to have added value. This research uses a qualitative approach. Data collection was carried out through participant observation, interviews, documentation studies and conducting Focus Group Discussion (FGD) activities with schools. Sample and Focus Locations were determined based on the purposive sampling method from pre-eliminary study data sources. From this research, data was obtained that Shipping Vocational Schools in North Jakarta have not optimally utilized local-based knowledge to increase regional and student potential.